Human exposure to trace metals and arsenic via consumption of fish from river Chenab, Pakistan and associated health risks. (February 2017) - Alamdar, Ambreen; Eqani, Syed Ali Musstjab Akber Shah; Hanif, Nida; Ali, Syeda Maria; Fasola, Mauro; Bokhari, Habib; Katsoyiannis, Ioannis A.; Shen, Heqing
Abstract: This study provided the first hand data of trace elements into fish muscles (N = 65) collected from river Chenab in Pakistan during 2013, using inductively coupled plasma mass spectrometry (ICP-MS). We monitored the health risk associated with consumption of contaminated fish of river Chenab, by the local population. The mean concentrations (μg/g, wet weight), in descending order were: Zn (35.5–54.4), Cu (1.38–4.57), Mn (2.43–4.5), As (0.23–1.21), Cr (0.21–0.67), Ni (0.14–0.34), Pb (0.14–0.31), Co (0.09–0.12), Cd (0.07–0.12) with higher concentration to be observed in the herbivore fish species (i.e., Cirrhinus reba and Catla catla ). The levels of trace elements in different fish species found in this study were compared with similar data worldwide, and with the international standards for consumption. The concentration (μg/g) of arsenic in many cases (>65%) exceeded the FAO/WHO expert committee on food additives permissible limits. From the human health point of view, this study highlights that the local inhabitants, (i.e., fisher folk communities and population frequently consuming fish at about 100 g/day) along the river Chenab are exposed chronically to arsenic pollution with carcinogenic (10 −4 to 10 −6 ) and non-carcinogenic (THQ>1) risks, especially from the intake of Cirrhinus reba . Highlights: Trace metals and arsenic levels were assessed in fish collected from River Chenab. First time data of trace elements and arsenic in the Pakistani fish measured by ICP-MS. Herbivore species showed highest accumulation of trace metals than carnivores. Arsenic in 65% of cases exceeded the proposed limit in fish muscles. THQs for arsenic reflected both carcinogenic and non-carcinogenic human health risk.